The HI‐STAR study: resource utilization and costs associated with serologic testing for antibody‐positive patients at four United States medical centers. Issue 2 (3rd April 2013) - Mazonson, Peter; Efrusy, Molly; Santas, Chris; Ziman, Alyssa; Burner, James; Roseff, Susan; Vijayaraghavan, Arthi; Kaufman, Richard
<x xml:space="preserve">Abstract</x> Background Little is known about how the resource utilization and costs of serologic work ups for positive antibody screens vary across subpopulations based on diagnosis, transfusion history, and serologic testing history. Study Design and Methods Detailed data were collected on patient demographics, diagnoses, transfusion history, history of known allo‐ and autoantibodies, and specific serologic tests performed for 6077 consecutive serologic work ups in 3608 antibody‐positive patients between 2009 and 2011 at four US academic medical centers. Direct testing costs were also determined at each site for each serologic test performed to calculate total costs per work up and per patient over the duration of the study. Results The mean direct cost of serologic testing was $114 per work up and $195 per patient. The mean cost per patient was significantly higher for 12 of 19 diagnostic categories evaluated, including autoimmune hemolytic anemia (mean cost per patient, $1490; p < 0.001), hematologic malignancies ($640, p < 0.001), and transplant recipients ($462, p = 0.019). Patient transfusion and serologic testing characteristics associated with greatest increases in costs included history of a warm autoantibody ($626, p < 0.001) and more than five prior transfusions ($404, p < 0.001). Conclusion Antibody‐positive patients with complex diagnoses or transfusion histories require significantly more resources and incur greater cost to assess red blood cell antibody status.